Feasibility of Dried Blood Spots in Children with Behavioral Problems. Issue 4 (August 2020) - Kloosterboer, Sanne M.; van Eijk, Estelle; van Dijk, Monique; Dieleman, Gwen C.; Hillegers, Manon H. J.; van Gelder, Teun; Koch, Birgit C.; Dierckx, Bram
Abstract : Background: Minimally invasive sampling methods are important to facilitate therapeutic drug monitoring and pharmacokinetic research in children with behavioral problems. This study assessed the feasibility and pain of dried blood spot (DBS) sampling in this population. Methods: Repeated DBS sampling was performed in children with autism spectrum disorder (ASD) and severe behavioral problems using antipsychotic drugs, aged between 6 and 18 years. The child, guardian, and DBS performer assessed pain using the numeric rating scale (NRS-11) or 5-face Faces Pain Scale. The influence of age, sex, and the fingerprick performer on the child's pain intensity was analyzed using linear mixed models. Results: Overall, 247 fingerpricks were performed in 70 children. Seven children refused all DBS sampling. The median (interquartile range) NRS-11 pain scores were 2 (3) rated by children, 3 (2.5) by guardians, and 2 (2) by fingerprick performers. The child's age and sex, and fingerprick performer had no significant influence on pain intensity. Conclusions: DBS sampling could be performed in most children with ASD and severe behavioral problems. However, 1 in 5 children refused one or more DBS fingerpricks owing to distress. Most expressed minimal pain (NRS < 4). Repeated sampling with DBS is feasible in children with ASD and severe behavioral problems.